2019
DOI: 10.1590/1980-4415v33n63a18
|View full text |Cite
|
Sign up to set email alerts
|

Dinâmicas de Reflexão e Colaboração entre Professores do 1.° Ciclo num Estudo de Aula em Matemática

Abstract: Resumo Com este artigo, pretendemos mostrar como é que professoras do 1.° ciclo que ensinam Matemática e que participam num estudo de aula desenvolvem os seus modos de reflexão e colaboração. A investigação é de natureza qualitativa e interpretativa com design de estudo de caso. Os resultados mostram que o envolvimento em momentos de planejamento de tarefas e de análise do trabalho dos alunos, quando as professoras refletem sobre a prática e para a prática, as ajuda a desenvolverem relações de colaboração, pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Examining the dynamics of collaboration and reflection in lesson study, Quaresma and Ponte (2019) emphasize that the involvement of participants in a process in which they shared goals, facilitated the development of three levels of reflection. The first involves a shallow reflection, based on a description of events, in which teachers tend to associate students' difficulties with external factors.…”
Section: Lesson Studymentioning
confidence: 99%
See 3 more Smart Citations
“…Examining the dynamics of collaboration and reflection in lesson study, Quaresma and Ponte (2019) emphasize that the involvement of participants in a process in which they shared goals, facilitated the development of three levels of reflection. The first involves a shallow reflection, based on a description of events, in which teachers tend to associate students' difficulties with external factors.…”
Section: Lesson Studymentioning
confidence: 99%
“…Thus, the study showed that at the beginning of the process teachers tended to attribute the students' difficulties to their immaturity or to nature of the math itself. At the end, they began to identify the students' learning problems, and to suggest and establish ways to help them overcome difficulties, transposing the suggestions presented to the group into changes to be carried out in their practice (Quaresma & Ponte, 2019). Rincón and Fiorentini (2017) conducted an investigation into the educational process and learning by future educators in a Pedagogical Practices in Mathematics course.…”
Section: Lesson Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Although vast around the world, the literature on lesson studies presents few works that deal with reflection as an object of study. Still, the works by Lee (2008), Gutierrez (2015), Suh and Seshaiyer (2015), Pang and Marton (2017), Quaresma and Ponte (2019), Richit, Ponte, and Tomasi (2021), and Vieira (2021) seek to think, each one under a specific approach, the reflection engendered in lesson study.…”
Section: Lesson Studymentioning
confidence: 99%